GERBANG SALAM: Telaah atas Pelaksanaanya di Kabupaten Pamekasan - Hariyanto, Erie (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
Abstrac The realization of power decentralization motivates the awakening of Muslims to express Islamic aspirations. It mainly touches the application of Islamic law. In 2002, Pamekasan launched a Gerbang Salam (movement of Islamic community development).Â  It covers three folds, Aqidah (faith) sector, Islamic law and moral. They are expected to establish good Muslim personalities. To support this movement, the local government of Pamekasan institutes LP2SI. This institution faces many challenges. This article tries to evaluate the realization of Gerbang Salam program in its six years application. Kata-kata kunci Syariah Islam, umat Islam, Gerbang Salam